Muscle and Liver Insulin Resistance Indexes Derived From the Oral Glucose Tolerance Test - Abdul-Ghani, Muhammad A; Matsuda, Masafumi; Balas, Bogdan; DeFronzo, Ralph A (Diabetes care, 2007)
OBJECTIVE:--To derive indexes for muscle and hepatic insulin sensitivity from the measurement of plasma glucose and insulin concentrations during an oral glucose tolerance test (OGTT). RESEARCH DESIGN AND METHODS--A total of 155 subjects of Mexican-American origin (58 male and 97 female, aged 18-70 years, BMI 20-65 kg/m²) with normal glucose tolerance (n = 100) or impaired glucose tolerance (n = 55) were studied. Each subject received a 75-g OGTT and a euglycemic insulin clamp in combination with tritiated glucose. The OGTT-derived indexes of muscle and hepatic insulin sensitivity were compared with hepatic and muscle insulin sensitivity, which was directly measured with the insulin clamp, by correlation analysis. RESULTS:--The product of total area under curve (AUC) for glucose and insulin during the first 30 min of the OGTT (glucose₀₋₃₀[AUC] x insulin₀₋₃₀[AUC]) strongly correlated with the hepatic insulin resistance index (fasting plasma insulin x basal endogenous glucose production) (r = 0.64, P < 0.0001). The rate of decay of plasma glucose concentration from its peak value to its nadir during the OGTT divided by the mean plasma insulin concentration (dG/dt [divide sign] I) strongly correlated with muscle insulin sensitivity measured with the insulin clamp (P = 0.78, P < 0.0001). CONCLUSIONS:--Novel estimates for hepatic and muscle insulin resistance from OGTT data are presented for quantitation of insulin sensitivity in nondiabetic subjects.